Evaluation of Mechanical Properties of Warm-Mix Asphalt Mixtures Prepared with Sasobit and Zeolite Additives - Hasan, Wshyar M.; Yousif, Rana A.; Hesami, Saeid; Tayh, Sady A.; Jasim, Abbas F.; Ibrahim, Hawkar H. (Journal of Engineering and Technological Sciences, 2024)
This study aimed to evaluate the impact of different additive percentages on the mechanical properties and durability of warm-mix asphalt. Two types of additives, Sasobit as an organic additive and Zeolite as a water-based additive, along with bituminous foam, were used at 2%, 4%, and 6% levels in modified asphalt mixes. Rutting resistance, moisture susceptibility, and cracking resistance were assessed using semi-circular bending tests, dynamic creep tests, and indirect tensile strength tests, respectively. Additionally, a two-dimensional performance interaction diagram was developed. The results indicated that incorporating different percentages of Sasobit and Zeolite additives improved rutting and cracking resistance, respectively. Zeolite showed a positive impact on enhancing the resistance of the asphalt mixture against moisture susceptibility, while Sasobit had a negative effect. Moreover, the influence of these additives on mechanical performance intensified with increasing percentages. Notably, the mixture containing 6% Zeolite demonstrated the highest resistance to moisture susceptibility, while the mixture with 6% Sasobit showed the lowest. Furthermore, the performance interaction diagram results suggested that using 4% and 6% Zeolite along with 4% Sasobit is optimal for rutting and cracking resistance. Considering the degradation mechanisms of moisture susceptibility, rutting, and cracking, mixtures with 6% Zeolite and 4% Zeolite exhibited satisfactory performance against these factors.